Análise experimental de vigas de concreto armado com diferentes tipos de armadura de cisalhamento - SOUZA, Diego Ferreira de (2022)
The beams are structural elements of great importance for the transfer of vertical forces, and are generally sized to resist transversal forces (bending and shear stresses). In order to provide better ductility, it is necessary that the beams exhibit shear force greater than the bending force; this can be provided by different types of transverse reinforcements. Therefore, this research aims to verify experimentally and compare the reinforcements by conventional stirrup, type W stirrup, and stud stirrup. Thereby, beams were tested in reinforced concrete using conventional stirrup, proposed stirrup type "W" with and without hook, and stud rail steel connectors. All the beams used a transverse reinforcement ratio equivalent to 0.24, except for beams with "W" type stirrup, whose value is 0.25. The experimental program involves confection, instrumentation, concreting and testing of beams. The main results were: (i) For loads greater than 300 kN, the beam with conventional stirrup presented greater resistance than the others, however, the beam with hook stirrup W presented approximate resistance; (ii) The non-hooked W beam did not present satisfactory results in terms of bending due to the need for better anchoring, thus the beam with hooked W-beam was more efficient in the transfer of forces. For this reason, it is possible to note a practical applicability of the W-type stirrup as an alternative to the use of conventional stirrups on site. In addition, the analysis presented that the internal reinforcement may present gains in productivity during execution.